Puerto Rico, a Sick Social Body: from Oblivion to Memory. A Review of some of the Health Crises and Pandemics in our Recent History - Lebrón, Rafael (MEDICA REVIEW. International Medical Humanities Review / Revista Internacional de Humanidades Médicas, 2021)
Health and disease are always present in the historical evolution of the human being. The year 2020 has been presented as an extraordinary one in the recent history of humanity with the development and spread of the Covid-19 coronavirus pandemic throughout the planet. Puerto Rico has not been exempt from these events. Excuse and necessity for the Covid-19, its social impact forces us to make an approach of the previous health experiences most relevant in the history of the country to understand the Puerto Rican context in its scope and limitations to achieve effective control of the current pandemic.